Development of land based mobile mapping system using GPS and close range photogrammetry technique - Ses, Sahrum; Ahmad, Anuar; Wong, Tony Chee Siang (2006)
The development of Mobile Mapping System (MMS) is still at initial stage in Malaysia. The research in MMS has been carried out quite awhile since the first prototype introduced by the Center of Mapping at The Ohio State University (Bossler et.al.,1991). This system integrates some navigation sensor such as Global Positioning System (GPS), inertial navigation system (INS) and mapping sensor such as Charge Coupled Device (CCD) camera. The strength of the MMS lays in their ability to directly georeferenced their mapping sensor by GPS. A mapping sensor is georeferenced when it is positioned and orientated relative to a known mapping coordinate frame. Once georeferenced, the mapping sensor can be used to determine the position of object points bases on the digital image in the same mapping coordinate frame. This research concentrates on georeferencing the geographic and topographic features and updating a GIS (Geographic Information System) base map using consumer digital camera and GPS positioning technique. The GPS provides the position of the camera and the images from the camera are used to determine the geodetic position of the object points using PhotoModeler software and developed program.